Xie Jiao as “Criminal Religious Movements”: A New Look at Cult Controversies in China and Around the World - Introvigne, Massimo (The journal of CESNUR, 2018)
Chinese Criminal Code punishes those active in a xie jiao with imprisonment from three to seven years. Xie jiaois translated in the English versions of Chinese official documents as “evil cults,” but the translation is inaccurate. As “heterodox teachings,” xie jiao have been banned in China since the Ming era, and the Communist regime inherited the practice of publishing lists of xie jiaofrom imperial and republican China. Historically, teachings were often declared “heterodox” for political rather than purely theological reasons, and today the definitions of xie jiao in Chinese documents and case law are vague at best. The paper argues that taking inspiration on Western categories such as “heresy” and “cult” would not help the Chinese in defining xie jiao in more precise terms, since these Western terms were also historically fluid and easily used as tools for discriminating unpopular groups. In recent years, the Chinese authorities did invite to their anti-xie-jiaoevents, in addition or as an alternative to militant anti-cultists, Western scholars of new religious movements, including the author of this paper. I tried to introduce a new category, “criminal religious movements,” including groups that either (or both) consistently practice and justify common crimes such as terrorism, child abuse, rape, physical violence, homicide, and serious economic crimes, as opposite to the vague or imaginary crimes of “being a cult” or “brainwashing members.” The paper argues that there would be definite advantages in replacing categories such as xie jiao, “destructive cults,”and “extremist religions” (the latter now fashionable in Russia) with “criminal religious movements,” a notion that would refer to ascertained crimes perpetrated by each movement rather than to notions so vague that they become dangerous for religious liberty.